Teologi Penghormatan dari Budaya Kong Tek dengan Budaya Kristen - Noveni Diana Suwita; Yonathan Yakub Mononimbar; Agung Dian Rengganis (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
Respect for ancestors is a key aspect of Chinese culture, expressed through the practice of Kong Tek, a ritual ceremony that includes prayers, offerings, and the burning of symbolic items to support the well-being of ancestral spirits in the afterlife. In contrast, Christian theology emphasizes salvation through faith in Jesus Christ and prohibits practices that involve contact with spirits. This journal analyzes the differences and similarities between Christian teachings and Kong Tek practices and offers advice for Chinese Christians in balancing their faith and culture.